Спечені тверді сплави марок ВК6 та ВК8, отримані різними методами переробки техногенної сировини - Бондаренко, В.П.; Мартинова, Л.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Results are given of all-round studies of physico-mechanical properties and structure of recovered
sintered hard alloys of WC-6Co and WC-8Co grades produced by different manufacturers
with the use of zinc («Karma», Svetlovodsk, «Tekhnokor», Kharkov) and thermochemical carbon
black-free («Alcon-Tverdosplav, Kiev» reprocessing procedures. It has been found that the stress
intensity factor, hardness, bending and compression strength limits essentially depend on the
method of recovering mixtures from technogenic raw materials as well as on additional reprocessing
operations.